2012
DOI: 10.2174/1874303x01205010004
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis Catheter Placement Techniques

Abstract: The success of catheter placement is critically important for the ability to stay on peritoneal dialysis over the long-term. Nephrologists have used percutaneous placement with or without fluoroscopic guidance and placement using peritoneoscopic guidance to place these catheters. Complications can be divided into early, within 14 days, and late complications, those arising more that 14 days after the procedure. The main post-procedure complications are infection, leakage, and obstruction. Results of non-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…1,3 Twisted catheter is typically associated with surgical complications during catheter insertion. 4 In our patient, the twisted catheter occurred during chronic catheter-site care. Ultrafiltration problems did not occur, and catheter malposition was ruled out by abdominal imaging.…”
Section: Discussionmentioning
confidence: 70%
“…1,3 Twisted catheter is typically associated with surgical complications during catheter insertion. 4 In our patient, the twisted catheter occurred during chronic catheter-site care. Ultrafiltration problems did not occur, and catheter malposition was ruled out by abdominal imaging.…”
Section: Discussionmentioning
confidence: 70%
“…The standard peritoneoscopic technique (Y-TEC) has been described elsewhere. 5 In both methods, patients were instructed to wash the whole body with chlorhexidine and to empty their bladder and bowel immediately prior to the procedure. Laxatives were used starting few days before the procedure to ensure patients had a bowel movement on the day of the procedure.…”
Section: Catheter Insertionmentioning
confidence: 99%
“…Several authors found a benefit with laparoscopic insertion, while the others showed, they were equivalent in complications and catheter survival. [ 1 3 ] Despite different opinions of experts and different results of randomised clinical trials and meta-analyses, laparoscopic insertion of PD catheter is becoming widely accepted method for gaining of peritoneal access.…”
Section: Introductionmentioning
confidence: 99%